PERUBAHAN SPASIAL TUTUPAN LAHAN DI DAS CITARUM HULU - Sri Malahayati Yusuf (Graduate School Bogor Agricultural University (SPs IPB), 2018)
Land cover is one of factors which is important in watershed management. The changes of land cover in a watershed can affect the hydrology abstraction. Land cover of upstream Citarum watershed is potentially changes. Economy, social, population, and natural hazard are factors that affect the change in land cover. The aim of this research were to analyze spatial change of land cover in upstream Citarum watershed period 2006-2014 and predicting future land cover of 2030 as usual and applying a policy to conserve paddy field and forest. Analysis was carried out applying Cellular automata markov chain of land cover spatial model. The result showed that Kappa and total accuracy for image classification were 0.89 and 0.92. Dominant land cover type in upstream Citarum watershed was paddy field of 25.99 – 26.06%. The average of land cover changes approximately < 1% with conversion of paddy field to built up area is the dominant change. Model validation of 2014 predicted land cover was 0.992, while Kappa for optimum iteration of 7 was 0.994. The land cover for period 2006-2030 was change approximately < 1%. The types of land cover that increase in 2030 were built up area and mixed farming of 0.21% and 0.11%, respectively, while plantation forest, moor, paddy field, and bareland were decreasing approximately 0.17, 0.23, 0.62 and 0.02%. The predicted land cover of 2030 under protection of paddy filed and forest scenario was trigger the increasing of mixed farming 0.36%, while moor and bareland were decrease of 0.22 and 0.10%.